2017
DOI: 10.4172/2254-609x.100047
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Transmitted Infections, Pelvic Inflammatory Disease, and the Role from Intrauterine Devices: Myth or Fact?

Abstract: Connections among Intra Uterine Devices (IUD), Sexually Transmitted Diseases (STDs) and Pelvic inflammatory disease (PID) still bring doubts for health professionals; Our goal is to understand better these associations. We searched the PubMed database for articles including evidence about these topics. A common outcome found is the superiority of levonorgestrel (LNG) IUD over NOVA T (copper) device regarding clinical performance and PID rates. The modern IUDs do not elevate the risk of getting PID; however thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…1,11,25 In the present study, the nulliparous tended to experience greater difficulty with the insertion of the LNG-IUS. One explanation for this could be because for many years, the insertion of a copper IUD in nulliparous was contraindicated, 11 which has led to a lower ability of the professionals for inserting the LNG-IUS in this group of women.…”
Section: Discussionmentioning
confidence: 49%
See 4 more Smart Citations
“…1,11,25 In the present study, the nulliparous tended to experience greater difficulty with the insertion of the LNG-IUS. One explanation for this could be because for many years, the insertion of a copper IUD in nulliparous was contraindicated, 11 which has led to a lower ability of the professionals for inserting the LNG-IUS in this group of women.…”
Section: Discussionmentioning
confidence: 49%
“…The LNG-IUS expanded the indications for intrauterine devices, including contraception for nulliparous and this indication became more frequently and supported by scientific evidence. 9,11,25 Parity has also been considered a factor that may be related to the difficulty in insertion of the LNG-IUS 9,10 although some studies reported no difficulty in the insertion in nulliparous. 1,11,25 In the present study, the nulliparous tended to experience greater difficulty with the insertion of the LNG-IUS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations